Infection in a female Komodo dragon (Varanus komodoensis) caused by Mycobacterium intracellulare: a case report - M. Skoric; V. Mrlik; J. Svobodova; V. Beran; M. Slany; P. Fictum; J. Pokorny; I. Pavlik (Veterinární Medicína, 2012)
In early 2002, a bean-like whitish nodule 2 × 1 × 1 cm in size was diagnosed on the tongue of a female Komodo dragon (Varanus komodoensis) kept in a zoological garden in the Czech Republic. The nodule was removed at surgery and histopathological examination revealed a specific granulomatous inflammation. The granuloma contained a necrotic mass surrounded by a variable layer of palisading epithelioid macrophages and multinucleated giant cells with a variable admixture of lymphocytes and plasma cells. Signs of mineralisation within the granuloma were not observed. Using Ziehl-Neelsen (ZN) staining the presence of acid-fast rods (AFR) was determined and the presence of mycobacteria was confirmed by PCR. Four years later, this female died after multiple injuries caused by a male during mating. Necropsy and histopathological examinations revealed granulomatous pneumonia and myocarditis with ZN-positive AFR within granulomas. Mycobacteria were cultured from 13 of 19 tissue samples: Mycobacterium intracellulare was confirmed by sequencing of isolates from multiple affected organs including the respiratory tract, tail muscle, inguinal lymph nodes and blood; Mycobacterium sp. were also isolated from the tongue. In addition, mycobacteria were detected in 15 (46.9%) of 32 environmental samples examined in both years. M. intracellulare was detected in water sediment from the female's terrarium in 2002, and in faeces and peat from the terrarium and in water sediment from the male terrarium in 2006. Except for M. intracellulare (n = 4), M. smegmatis (n = 1), M. a. hominissuis (n = 3), M. fortuitum (n = 2), M. interjectum (n = 1), M. peregrinum/alvei/septicum (n = 1) and Mycobacterium sp. (n = 2) were also isolated from different environmental samples.